2016
DOI: 10.1088/1748-9326/11/12/124019
|View full text |Cite
|
Sign up to set email alerts
|

Soil greenhouse gas emissions reduce the contribution of mangrove plants to the atmospheric cooling effect

Abstract: Mangrove soils have been recognized as sources of greenhouse gases, but the atmospheric fluxes are poorly characterized, and their adverse warming effect has rarely been considered with respect to the potential contribution of mangrove wetlands to climate change mitigation. The current study balanced the warming effect of soil greenhouse gas emissions with the plant carbon dioxide (CO 2 ) sequestration rate derived from the plants' net primary production in a productive mangrove wetland in South China to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 37 publications
3
49
1
Order By: Relevance
“…The K. obovata mangrove swamps in the Pearl River Estuary, which received anthropogenic nutrients from the delta and nearby polluted rivers, had fluxes as high as 23.83 μ mol N 2 O m −2 h −1 , 5168.62 μ mol CH 4 m −2 h −1 , and 20.56 mmol CO 2 m −2 h −1 in the summer (Chen et al ). In the present study, our study sites did not receive direct discharge of wastewater from the adjacent aquaculture pond and the fluxes of the greenhouse gases were low, less than 2.08 mmol CO 2 m −2 h −1 , 2.62 μ mol CH 4 m −2 h −1 , and 0.45 N 2 O μ mol m −2 h −1 , and even lower than other K. obovata mangroves in Jiulong River Estuary (Chen et al ). Actually, the sediment OC and TN concentrations at our sites were also lower than those reported in the above mangroves (Chen et al , ).…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…The K. obovata mangrove swamps in the Pearl River Estuary, which received anthropogenic nutrients from the delta and nearby polluted rivers, had fluxes as high as 23.83 μ mol N 2 O m −2 h −1 , 5168.62 μ mol CH 4 m −2 h −1 , and 20.56 mmol CO 2 m −2 h −1 in the summer (Chen et al ). In the present study, our study sites did not receive direct discharge of wastewater from the adjacent aquaculture pond and the fluxes of the greenhouse gases were low, less than 2.08 mmol CO 2 m −2 h −1 , 2.62 μ mol CH 4 m −2 h −1 , and 0.45 N 2 O μ mol m −2 h −1 , and even lower than other K. obovata mangroves in Jiulong River Estuary (Chen et al ). Actually, the sediment OC and TN concentrations at our sites were also lower than those reported in the above mangroves (Chen et al , ).…”
Section: Discussionmentioning
confidence: 46%
“…). These two sites displayed good conditions and the density and canopy height of the mangroves were 0.9 stems m −2 and 5.5 m, respectively (Chen et al ).…”
Section: Study Area and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected global NPP and NEP data from online database resources (Luyssaert et al 2007;Luyssaert 2009) and published literature (Li et al 2006;Yan et al 2006;Huang et al 2007;Yang et al 2007;Ma et al 2008;Xiao et al 2010;Chen et al 2011a;Tan et al 2011;Tang et al 2011Tang et al , 2015bTang et al 2016a, Chen et al 2016aSong et al 2017). These data included location coordinates and meteorological information, such as mean annual temperature (MAT) and mean annual precipitation (MAP).…”
Section: Literature Survey For Npp and Nep Comparisonmentioning
confidence: 99%
“…Mangrove wetlands are a potential source for atmospheric CH 4 , but there remain considerable uncertainties regarding the importance of mangrove wetlands for contributing climate warming [22]. Through a field study at three tidal zones of two mangrove ecosystems in southeastern China, Zheng et al found highly variable CH 4 emission patterns among the three zones and attributed this phenomenon to the heterogeneity in the mangrove soil environment [23].…”
mentioning
confidence: 99%